SOME DEBATABLE ISSUES CONCERNING THE HISTORY OF THE COMPOSITION OF THE 15TH-CENTURY MASNAVI “YUSUF AND ZULAYKHO” CREATED IN BALKH - ORIPOV JAHONGIR RAUPOVICH (International Journal of Literature and Language Studies, 2026)
This article analyzes controversial issues related to the history of composition, authorship, and textual features of the 15th-century masnavi “Yusuf and Zulaykho,” created in Balkh. It emphasizes that the story of Yusuf is a widely circulated transnational motif in Eastern literature and exists in various versions in different languages and authored by different writers. The study highlights two competing views regarding the date of the work’s composition—Hijri 812 (1409–1410) and Hijri 874 (1469)—based on abjad calculations and textual differences in manuscript copies. Furthermore, the views of scholars such as Abdurauf Fitrat, Mehmed Fuad Köprülü, Edgard Blochet, and Khalida Dolu are comparatively analyzed, and the attribution of the work to Durbek or other authors is discussed. The article concludes by substantiating the necessity of producing a critical scholarly edition by unifying all available manuscripts.